Diseño de la webs para la estimación de costos y beneficios de los proyectos de hidrocarburos del área de desarrollo de nuevos campos de cepcolsa (2015)
The methodology used by the authors in the development of the project and the work of degree, allowed the construction of a WBS type, for the projects of crude production of the company CEPCOLSA, which managed to link directly with the cost benefit evaluation, allowing thus, the comparison between similar projects and considerably streamlining the planning and decision-making processes of investment in new projects in the New Assets area of the company.